Recent advances in biodiesel production: challenges and solutions - Mathew, Gincy Marina; Raina, Diksha; Narisetty, Vivek; Kumar, Vinod; Saran, Saurabh; Pugazhendi, Arivalagan; Sindhu, Raveendran; Pandey, Ashok; Binod, Parameswaran (Elsevier, 2021)
Mono alkyl fatty acid ester or methyl ethyl esters (biodiesel) are the promising alternative for fossil fuel or petroleum derived diesel with similar properties and could reduce the carbon foot print and the greenhouse gas emissions. Biodiesel can be produced from renewable and sustainable feedstocks like plant derived oils, and it is biodegradable and non-toxic to the ecosystem. The process for the biodiesel production is either through traditional chemical catalysts (Acid or Alkali Transesterification) or enzyme mediated transesterification, but as enzymes are natural catalysts with environmentally friendly working conditions, the process with enzymes are proposed to overcome the drawbacks of chemical synthesis. At present 95% of the biodiesel production is contributed by edible oils worldwide whereas recycled oils and animal fats contribute 10% and 6% respectively. Although every process has its own limitations, the enzyme efficiency, resistance to alcohols, and recovery rate are the crucial factors to be addressed. Without any benefit of doubt, production of biodiesel using renewable feedstocks and enzymes as the catalysts could be recommended for the commercial purpose, but further research on improving the efficiency could be an advantage.
Keywords: Biodiesel; Catalyst; Lipase; Greenhouse gas; Nanocatalyst; Immobilized enzymes